The Role of Parents in Increasing Children's English Vocabulary in Kelambir V Kebun - Efrizah, Doni; Sari, Indah; Putri, Vivi Oxana (JL3T (Journal of Linguistics, Literature and Language Teaching), 2024)
This research aims to discuss the important role of parents in increasing children's English vocabulary because there are still many parents who lack a role in improving children's English skills, especially increasing English vocabulary to improve language skills. Language skills are an important aspect of children's language development and have a significant impact on children's communication abilities. This study explored various ways parents can play a role in expanding children's English vocabulary. This research method involved a review of literature investigating the role of parents in children's vocabulary development. The research method used was qualitative research. Nine parents in Kelambir V Kebun Village were selected purposely as the subject of the research. Interview and observation were used to collect the data. The research results showed that parents had a strong influence in enriching children's vocabulary through speaking models, providing visual stimulation, and providing access to various English learning resources. In addition, this research also underlined the importance of creating an environment that supports language learning, adopting a positive approach, and understanding the child's developmental level. This research implied that parents have a central role in helping children acquire strong English language competence. By actively involving themselves in the language learning process, parents could make a significant contribution to the growth of their children's English vocabulary, but there were still many parents who did not have much effort and methods to increase their children's English vocabulary so that children had insufficient vocabulary.